Influence of meteorological factors on modelling the thermal regime of a river. (January 2020) - Neagoe, A; Tică, E I; Ahmad-Rashid, K; Popa, F; Popa, B
Abstract: The aim of the paper is to determine whether the use of several parameters in a multi-linear regression equation can estimate the evolution of the water temperature. Thus, a simplified physical-based non-spatial model is designed for calculating the time variation of river water temperature. The water-to-air transfer function is constructed using the recorded environmental factors, instead the flow rate, respectively the depth of water in the riverbed, is assumed to be constant over the 31-days analysis period. A comparison between logistic relation, according to a classical proposed model and multiple linear regression with four parameters is done.